2022
DOI: 10.1155/2022/1516633
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Adjuvant Treatment of Primary Nephrotic Syndrome in Pediatric Patients with Chinese Medicine

Abstract: Objective. Current study aimed to investigate the benefits of adjuvant therapy with traditional Chinese medicine on the pediatric primary nephrotic syndrome. Methods. A total of 455 patients with PNS admitted to our hospital from January 2010 to January 2019 were divided into the traditional Chinese medicine group (n = 217) and the control group (n = 238). The control group received conventional Western medical treatment, and the traditional Chinese medicine group was treated with traditional Chinese medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Yuebi Jiazhu Tang was used as adjuvant therapy for primary nephrotic syndrome in children. The remission rate and non-recurrence rate in the adjuvant treatment group with TCM were significantly higher than those in the non-treatment group (91.2 vs. 84.8% and 20.7 vs. 11.3%, respectively) ( Wu et al, 2022 ). Abelmoschus manihot alone or combined with losartan potassium was used to treat patients with non-NS primary glomerular disease, including MCD and FSGS, and the results showed that Abelmoschus manihot could significantly reduce the level of proteinuria ( Zhang et al, 2014 ).…”
Section: Clinical Studies On Treating Podocytopathies With Tcmmentioning
confidence: 99%
“…Yuebi Jiazhu Tang was used as adjuvant therapy for primary nephrotic syndrome in children. The remission rate and non-recurrence rate in the adjuvant treatment group with TCM were significantly higher than those in the non-treatment group (91.2 vs. 84.8% and 20.7 vs. 11.3%, respectively) ( Wu et al, 2022 ). Abelmoschus manihot alone or combined with losartan potassium was used to treat patients with non-NS primary glomerular disease, including MCD and FSGS, and the results showed that Abelmoschus manihot could significantly reduce the level of proteinuria ( Zhang et al, 2014 ).…”
Section: Clinical Studies On Treating Podocytopathies With Tcmmentioning
confidence: 99%
“…[1] It mainly occurs in children and adolescents, and its incidence rate is about (2–16.9) per 100,000. [2] Most studies believed that the incidence of PNS was closely related to genetics, infection, immunity, drugs, and environment, especially upper respiratory tract infection, which was considered as an important factor for the frequent recurrence of PNS in children. [3] After admission, children generally stayed in hospital for a long time, which affected their normal life, learning and social interaction, mainly included behavioral abnormalities, excessive activity, crying, aggression, depression, etc.…”
Section: Introductionmentioning
confidence: 99%